Metal part and preparation method thereof, and electronic product housing
By forming a porous anodized film with gradient changes on the surface of the metal substrate, the shortcomings of existing aluminum alloy metal products in terms of appearance texture and touch are solved, the gradient effect of ceramic texture to metal texture is achieved, and wear resistance and resistance are improved. Corrosion performance.
Patent Information
- Application Number
- CN202111005148.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-08-30
AI Technical Summary
Existing aluminum alloy metal products cannot meet the market's gradual demand for ceramic and metal texture in terms of appearance texture and touch, and at the same time lack good wear and corrosion resistance.
By forming an anodized film composed of a first porous layer and a second porous layer on the surface of the metal substrate, the pore size of the first porous layer is 1-20 nm and the pore size of the second porous layer is 20-40 nm , the thickness of each layer changes gradiently, thereby achieving a gradient appearance effect from the ceramic texture to the metal texture, and improving wear and corrosion resistance.
It realizes the appearance effect of the ceramic texture of metal parts to the metal texture, and at the same time has good wear and corrosion resistance, meeting the market's demand for high quality and high performance.
Smart Images

Figure HDA0003236938370000011 
Figure HDA0003236938370000012 
Figure HDA0003236938370000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, and in particular to a metal part and a preparation method thereof, and an electronic product housing. Background Art
[0002] With the improvement of consumption level, consumers pay more and more attention to the texture and touch of electronic products, not only the quality of electronic products. The existing aluminum alloy metal products with single metal texture or single imitation ceramic texture effect can no longer meet the current market demand. Summary of the invention
[0003] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a metal part and a preparation method thereof, and an electronic product housing. The metal part has an appearance effect of gradually changing from ceramic texture to metal texture, and has good wear resistance and corrosion resistance.
[0004] The first aspect of the present invention is to provide a metal part, comprising: a metal substrate and an anodized film located on the surface of the metal substrate, the anodized film comprising a first porous layer located on the metal substrate and a second porous layer located on the first porous layer, the pore size of the first porous layer is 1-20 nm, the pore size of the second porous layer is 20-40 nm, and the thickness of the first porous layer or the second porous layer varies in a gradient.
[0005] Preferably, the metal substrate has a first end and a second end, and along an extension direction of the metal substrate from the first end to the second end, a thickness of the first porous layer or the second porous layer gradually decreases.
[0006] Preferably, along the extension direction from the first end to the second end of the metal substrate, the thickness of the first porous layer gradually decreases.
[0007] Preferably, along the extension direction from the first end to the second end of the metal substrate, the first porous layer has a starting end and an ending end, the thickness of the first porous layer at the starting end is 2-6 μm, and the thickness of the first porous layer at the ending end is 0-10 nm.
[0008] Preferably, the second porous layer has a thickness of 2-20 μm.
[0009] Preferably, along the extending direction from the first end to the second end of the metal substrate, the thickness of the second porous layer gradually decreases.
[0010] Preferably, along the extension direction from the first end to the second end of the metal substrate, the second porous layer has a starting end and an ending end, the thickness of the starting end of the second porous layer is 2-20 μm, and the thickness of the ending end of the second porous layer is 0-100 nm.
[0011] Preferably, the thickness of the first porous layer is 2-6 μm.
[0012] Preferably, the metal substrate comprises aluminum or an aluminum alloy.
[0013] Preferably, a sealing layer is provided on the surface of the anodized film away from the metal substrate.
[0014] The second aspect of the present invention is to provide a method for preparing the aforementioned metal part, comprising the following steps:
[0015] Immersing the metal substrate in an electrolyte for a first anodization to form a second porous layer on the metal substrate, and immersing the metal substrate having the second porous layer in the electrolyte for a second anodization to form a first porous layer between the metal substrate and the second porous layer, wherein the voltage of the first anodization is 10-30V, and the voltage of the second anodization is 8-12V;
[0016] Wherein, during the first anodization, the time for which different regions of the metal substrate are immersed in the electrolyte is controlled to change gradually so that the thickness of the second porous layer changes gradually, or, during the second anodization, the time for which different regions of the metal substrate are immersed in the electrolyte is controlled to change gradually so that the thickness of the first porous layer changes gradually.
[0017] Preferably, the total oxidation time of the first anodization is 10-40 minutes.
[0018] Preferably, the total oxidation time of the second anodization is 40-100 minutes.
[0019] Preferably, the electrolyte comprises: 20-200 g / L sulfuric acid and 0-50 g / L organic acid.
[0020] Preferably, before the first anodizing treatment, the metal substrate is pre-treated, and the pre-treatment includes at least one or more of CNC, grinding, polishing, sandblasting, degreasing, neutralization and water washing.
[0021] Preferably, after the second anodization, the anodized film is sealed.
[0022] A third aspect of the present invention is to provide an electronic product housing, comprising the aforementioned metal piece.
[0023] The present invention arranges the anodized film located on the metal substrate to include a first porous layer and a second porous layer located on the first porous layer, and the pore size of the second porous layer is larger than the pore size of the first porous layer, and the pore size of each layer is controlled within the scope of the present application, so that the metal part presents a ceramic texture effect. In addition, the thickness of the first porous layer or the second porous layer changes in a gradient, and the metal part gradually changes from a ceramic texture to a metallic texture along the direction in which the thickness of the first porous layer or the second porous layer gradually decreases, so that the metal part has an appearance effect of gradually changing from a ceramic texture to a metallic texture, and has good wear resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a schematic structural diagram of a metal part in one embodiment of the present invention;
[0025] Figure 2 is a schematic structural diagram of a metal part in another embodiment of the present invention;
[0026] Figure 3 is a schematic structural diagram of a metal part in another embodiment of the present invention;
[0027] Figure 4 is a schematic structural diagram of a metal part in yet another embodiment of the present invention;
[0028] Figure 5 is a scanning electron microscope topography image of one end of a metal member in one embodiment of the present invention;
[0029] Figure 6 3 is a scanning electron microscope image of the other end of the metal member in one embodiment of the present invention.
[0030] The reference numerals in the drawings of the specification are as follows:
[0031] 1. Metal substrate; 2. Anodic oxide film; 21. First porous layer; 22. Second porous layer. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] like Figure 1-3As shown, the present invention provides a metal part, comprising: a metal substrate 1 and an anodized film 2 located on the surface of the metal substrate, the anodized film 2 comprising a first porous layer 21 located on the metal substrate 1 and a second porous layer 22 located on the first porous layer 21, the pore size of the first porous layer 21 is 1-20 nm, the pore size of the second porous layer 22 is 20-40 nm, and the thickness of the first porous layer 21 or the second porous layer 22 varies in a gradient.
[0034] The present invention arranges the anodized film 2 located on the metal substrate 1 to include a first porous layer 21 and a second porous layer 22 located on the first porous layer 21, and the pore size of the second porous layer 22 is larger than the pore size of the first porous layer 21, and the pore size of the first porous layer 21 is in the range of 1-20 nm, and the pore size of the second porous layer 22 is in the range of 20-40 nm, so that the metal part presents a ceramic texture effect, and the thickness of the first porous layer 21 or the second porous layer 22 changes in a gradient, and the metal part gradually presents a metal texture from a ceramic texture along the direction in which the thickness of the first porous layer 21 or the second porous layer 22 gradually decreases, so that the metal part has an appearance effect of a gradual change from a ceramic texture to a metal texture, and has good wear resistance and corrosion resistance. It should be noted that the first porous layer 21 of the present application and the second porous layer 22 located on the first porous layer 21 are superimposed to present a ceramic texture. The first porous layer or the second porous layer alone presents a metal texture.
[0035] In the present invention, if the pore size of the second porous layer 22 is smaller than that of the first porous layer 21; or the pore size of the first porous layer 21 is not in the range of 1-20 nm; or the pore size of the second porous layer is in the range of 20-40 nm, the stacking of the first porous layer and the second porous layer cannot achieve a ceramic texture effect.
[0036] In some embodiments, Figure 1-3 As shown, the metal substrate 1 has a first end and a second end, and along the extension direction from the first end to the second end, the thickness of the first porous layer 21 or the second porous layer 22 gradually decreases, so that the metal part can achieve an appearance effect of transition from ceramic texture to metal texture.
[0037] In some embodiments, Figure 1-2As shown, along the extension direction from the first end to the second end of the metal substrate 1, the thickness of the first porous layer 21 gradually decreases. By stacking the first porous layer 21 and the second porous layer 22 in the metal part, the thickness of the first porous layer 21 is gradually reduced, the ceramic texture effect is gradually weakened, and the metal texture embodied by the second porous layer 22 is gradually presented. Preferably, along the extension direction from the first end to the second end of the metal substrate 1, the first porous layer 21 has a starting end and an end, the thickness of the starting end of the first porous layer is 2-6μm, and the thickness of the end of the first porous layer is 0-10nm. Thereby better realizing the appearance effect of the metal part gradually changing from ceramic texture to metal texture.
[0038] A specific implementation method, such as Figure 1 As shown, the thickness of the first porous layer 21 gradually decreases along the extension direction from the first end to the second end of the metal substrate 1. One of the two ends (end a and end b) of the metal substrate 1 can be used as the starting end, and the other end can be used as the end. For example, the end a of the metal substrate 1 is used as the starting end, and the end b is used as the end. The thickness of the first porous layer 21 gradually decreases as it extends from the end a of the metal substrate 1 to the end b. Along the extension direction from the end a of the metal substrate 1 to the end b, the metal part gradually changes from a ceramic texture to a metal texture.
[0039] Another specific embodiment, such as Figure 2 As shown, one of the two ends (end a and end b) of the metal substrate 1 can be used as the starting end, and any position between the two ends of the metal substrate 1 can be used as the end M. For example, the end a of the metal substrate 1 is used as the starting end, and any position between the two ends is used as the end M. The thickness of the first porous layer 21 gradually decreases as it extends from the end a of the metal substrate 1 to the end M. Along the extension direction from the end a of the metal substrate 1 to the end M, the metal part gradually changes from a ceramic texture to a metal texture. The distance between the end M and the end b of the metal substrate 1 can be controlled according to the actual appearance effect requirements.
[0040] In some embodiments, the thickness of the second porous layer 22 is 2-20 μm. By controlling the thickness of the second porous layer 22 within this range, it can better interact with the first porous layer 21 and achieve an appearance effect in which the texture of the metal part gradually changes from ceramic to metal.
[0041] In other embodiments, Figure 3As shown, along the extension direction from the first end to the second end of the metal substrate 1, the thickness of the second porous layer 22 gradually decreases. By stacking the first porous layer 21 and the second porous layer 22 in the metal part, the thickness of the second porous layer 22 is gradually reduced, the ceramic texture effect is gradually weakened, and the metal texture embodied by the first porous layer 21 is gradually presented. Preferably, along the extension direction from the first end to the second end of the metal substrate 1, the second porous layer 22 has a starting end and an end, the thickness of the starting end of the second porous layer 22 is 2-20μm, and the thickness of the end of the second porous layer 22 is 0-100nm. Thereby better realizing the appearance effect of the metal part gradually changing from ceramic texture to metal texture.
[0042] A specific implementation method, such as Figure 3 As shown, the thickness of the second porous layer 22 gradually decreases along the extension direction from the first end to the second end of the metal substrate 1. One of the two ends (end a and end b) of the metal substrate 1 can be used as the starting end, and the other end can be used as the end. For example, the end a of the metal substrate 1 is used as the starting end, and the end b is used as the end. The thickness of the second porous layer 22 gradually decreases as it extends from the end a of the metal substrate 1 to the end b. Along the extension direction from the end a of the metal substrate 1 to the end b, the metal part gradually changes from a ceramic texture to a metal texture.
[0043] Another specific embodiment, such as Figure 4 As shown, one of the two ends (end a and end b) of the metal substrate 1 can be used as the starting end, and any position between the two ends of the metal substrate 1 can be used as the end M. For example, the end a of the metal substrate 1 is used as the starting end, and any position between the two ends is used as the end M. The thickness of the second porous layer 22 gradually decreases as it extends from the end a of the metal substrate 1 to the end M. Along the extension direction from the end a of the metal substrate 1 to the end M, the metal part gradually changes from a ceramic texture to a metal texture. The distance between the end M and the end b of the metal substrate 1 can be controlled according to the actual appearance effect requirements.
[0044] In some embodiments, the thickness of the first porous layer 21 is 2-6 μm. By controlling the thickness of the first porous layer 21 within this range, it can better interact with the second porous layer 22 to achieve an appearance effect in which the texture of the metal part gradually changes from ceramic to metal.
[0045] In some embodiments, the metal substrate 1 may be an aluminum metal substrate or an aluminum alloy substrate, and the anodized film 2 is an aluminum oxide film.
[0046] In some embodiments, a sealing layer is provided on the surface of the anodized film 2 away from the metal substrate 1. Since the anodized film 2 has a porous structure, has strong adsorption, and is easily contaminated, the pore structure of the anodized film can be sealed by providing the sealing layer, thereby improving the corrosion resistance, contamination resistance, and wear resistance of the anodized film.
[0047] In some embodiments, according to the visual effect requirements of the metal part, the anodized film contains a dye, and the dye can be one or more of an azo dye, an anthraquinone dye, and a peptide cyanine dye.
[0048] A second aspect of the present invention is to provide a method for preparing the metal part as described above, comprising the following steps:
[0049] Immersing the metal substrate in an electrolyte for a first anodization to form a second porous layer on the metal substrate, and immersing the metal substrate having the second porous layer in the electrolyte for a second anodization to form a first porous layer between the metal substrate and the second porous layer, wherein the voltage of the first anodization is 10-30V, and the voltage of the second anodization is 8-12V;
[0050] Wherein, during the first anodization, the time for which different regions of the metal substrate are immersed in the electrolyte is controlled to change gradually so that the thickness of the second porous layer changes gradually, or, during the second anodization, the time for which different regions of the metal substrate are immersed in the electrolyte is controlled to change gradually so that the thickness of the first porous layer changes gradually.
[0051] Specifically, the metal substrate can be first subjected to a first anodization, and during the first anodization, the time for different regions of the metal substrate to be immersed in the electrolyte is controlled to form a second porous layer with a gradient thickness on the surface of the metal substrate; and then a second anodization is performed, and the voltage of the second anodization is lower than the voltage of the first anodization, so as to form a first porous layer between the metal substrate and the second porous layer, and finally obtain the aforementioned metal part. That is, the metal part includes a metal substrate and an anodized film located on the surface of the metal substrate, the anodized film includes a first porous layer located on the metal substrate and a second porous layer located on the first porous layer, the pore size of the first porous layer is 1-20 nm, the pore size of the second porous layer is 20-40 nm, and the thickness of the second porous layer varies in a gradient.
[0052] Alternatively, the metal substrate may be subjected to a first anodization to form a second porous layer of uniform thickness on the surface of the metal substrate; and then subjected to a second anodization, wherein the voltage of the second anodization is lower than the voltage of the first anodization, and the time for immersing different regions of the metal substrate in the electrolyte is controlled during the second anodization, so that a first porous layer is formed between the metal substrate and the second porous layer, and the thickness of the first porous layer varies in a gradient, and finally the aforementioned metal part is obtained. That is, the metal part includes a metal substrate and an anodized film located on the surface of the metal substrate, the anodized film includes a first porous layer located on the metal substrate and a second porous layer located on the first porous layer, the pore size of the first porous layer is 1-20 nm, the pore size of the second porous layer is 20-40 nm, and the thickness of the first porous layer varies in a gradient.
[0053] The present invention controls the voltage of the first anodization to be higher than the voltage of the second anodization, so that the anodized film transitions from the second porous layer to the first porous layer from the outside to the inside (along the direction close to the metal substrate). The voltage of the first anodization is 10-30V, and the pore size of the second porous layer is large. The voltage of the second anodization is 8-12V, so that the second porous layer extends branch-like pores on the side close to the metal substrate, and gradually forms the first porous layer. If the voltage of the first anodization is lower than the voltage of the second anodization, two porous layers cannot be formed. Moreover, if the voltage of the first anodization and the voltage of the second anodization are not within the aforementioned range, a structure in which the pore size of the first porous layer is 1-20 nm and the pore size of the second porous layer is 20-40 nm cannot be formed, and the effect of ceramic texture cannot be achieved.
[0054] In some embodiments, the anodic oxide film on the surface of the metal substrate can have a gradient change by controlling the time for which different regions of the metal substrate are immersed in the electrolyte. Specifically, the metal substrate can be gradually immersed in the electrolyte or gradually pulled out of the electrolyte during the anodizing process.
[0055] For example, in one embodiment, during the first anodization, the metal substrate is immersed in the electrolyte or pulled out from the electrolyte to achieve a gradient change of the anodized film. Figure 3To illustrate, end a of the metal substrate 1 is gradually immersed in the electrolyte until end b of the metal substrate 1 is invaded into the electrolyte, thereby realizing the first anodization of the metal substrate 1. Alternatively, the region from end a to end b of the metal substrate 1 is immersed in the electrolyte, and then the electrolyte surface is pulled upward from end b until end a of the metal substrate 1 is pulled out of the electrolyte surface, thereby realizing the first anodization of the metal substrate 1. The speed at which the metal substrate is immersed in the electrolyte or pulled out of the electrolyte can be uniform, uniformly accelerated or uniformly decelerated, and is selected according to the desired appearance effect. The size of the metal substrate is not limited and can be selected according to actual needs. In order to achieve a good first anodization effect, preferably, the total oxidation time is 10-40 minutes. Then a second anodization is performed. During the second anodization, the metal substrate is completely immersed in the electrolyte. Preferably, the oxidation reaction time is 40-100 minutes.
[0056] In another embodiment, the metal substrate is first anodized for the first time. During the first anodization, the metal substrate is completely immersed in the electrolyte. Preferably, the oxidation reaction time is 10-30 minutes. Then, the metal substrate is anodized for the second time. During the second anodization, the metal substrate is immersed in the electrolyte or pulled out of the electrolyte to achieve a gradient change of the anodized film. Figure 1 To illustrate, end a of the metal substrate 1 is gradually immersed in the electrolyte until end b of the metal substrate 1 is immersed in the electrolyte, thereby achieving the second anodization of the metal substrate 1. Alternatively, the region from end a to end b of the metal substrate 1 is immersed in the electrolyte, and then the electrolyte surface is pulled upward from end b until end a of the metal substrate 1 is pulled out of the electrolyte surface, thereby achieving the second anodization of the metal substrate 1. The speed at which the metal substrate is immersed in the electrolyte or pulled out of the electrolyte can be uniform, uniformly accelerated or uniformly decelerated, depending on the actual desired appearance effect. The size of the metal substrate is not limited and can be selected according to actual needs. In order to achieve a good second anodization effect, preferably, the total oxidation time is 40-100 minutes.
[0057] In some embodiments, the electrolyte includes: 20-200 g / L sulfuric acid, 0-50 g / L organic acid. The organic acid includes one or more of oxalic acid, succinic acid, citric acid and malic acid. The electrolyte containing the above components can better perform anodization.
[0058] In some embodiments, before the first anodizing treatment is performed, the metal substrate is pre-treated, and the pre-treatment includes at least one or more of CNC (computer digital control), grinding, polishing, sandblasting, degreasing, neutralization and water washing. The pre-treatment can improve the flatness and cleanliness of the metal surface, which is beneficial to the subsequent anodizing. Preferably, the metal substrate is pre-treated, and the pre-treatment includes CNC, grinding, polishing, sandblasting, degreasing, neutralization and water washing in sequence. The CNC, grinding, polishing, sandblasting, degreasing, neutralization and water washing are conventional CNC, grinding, polishing, sandblasting, degreasing, neutralization and water washing in the art, and are not limited here.
[0059] In some embodiments, after the second anodization, the anodized film is sealed to form a sealing layer on the surface of the anodized film to improve the corrosion resistance, pollution resistance and wear resistance of the anodized film.
[0060] In some embodiments, according to the visual effect requirements of the metal part, dyeing treatment can be performed after the second anodization, and the dye used in the dyeing treatment can be one or more of azo dyes, anthraquinone dyes and peptide cyanine dyes. After the dyeing treatment, the sealing treatment is performed.
[0061] The present invention also provides an electronic product housing, comprising the aforementioned metal piece.
[0062] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.
[0063] Example 1
[0064] This embodiment is used to illustrate the metal part and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0065] Pre-treatment: The aluminum alloy substrate is processed by CNC, grinding, polishing and other processes, and then degreased, neutralized and washed;
[0066] Anodizing: The pre-treated aluminum alloy substrate (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing. The voltage of the first anodizing is 18 V and the oxidation time is 25 min. Then the voltage is adjusted to 9 V, and the aluminum alloy substrate is pulled out of the electrolyte surface at a uniform speed from one end to the other end. The total oxidation time is 50 min. The electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20 ° C.
[0067] Dyeing treatment: After anodizing, the aluminum alloy substrate was ultrasonically treated, washed with water, and immersed in an organic dye tank for dyeing. The organic dye was Okuno Dye 502 with a concentration of 10 g / L, a temperature of 22°C, and a dyeing time of 5 min.
[0068] Sealing treatment: After dyeing, the aluminum alloy substrate was ultrasonically treated, washed with water and then put into a sealing tank. The sealing liquid brand was DX500 with a concentration of 10 g / L. The temperature was 93°C, the sealing time was 20 min, and then dried to obtain the metal part S1.
[0069] Scanning electron microscope test:
[0070] The microstructure of the anodized film was observed using a scanning electron microscope. Before the dyeing and sealing operation, 1 cm at one end and 1 cm at the other end of the metal part S1 were selected. 2 The anodized film on the left and right was subjected to gold spraying and then observed under a scanning electron microscope. The obtained electron microscope photograph is as follows Figure 5-6 shown.
[0071] The morphology of one end of the metal part S1 is as follows: Figure 5 As shown, the anodized film has a first porous layer 21 and a second porous layer 22 stacked together; the morphology of the other end of the metal member S1 is as shown in FIG. Figure 6 As shown, the anodized film has a second porous layer 22 .
[0072] The pore size of the first porous layer of the metal member S1 is 7-12 nm, and the pore size of the second porous layer is 25-35 nm.
[0073] Example 2
[0074] This embodiment is used to illustrate the metal part and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0075] Pre-treatment: The aluminum alloy substrate is processed by CNC, grinding, polishing and other processes, and then degreased, neutralized and washed;
[0076] Anodizing: The aluminum alloy substrate after pretreatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing. The voltage of the first anodizing is 18 V and the oxidation time is 25 min. Then the aluminum alloy substrate is pulled above the electrolyte without contacting the electrolyte. Then the voltage is adjusted to 9 V, and the aluminum alloy substrate is immersed in the electrolyte at a uniform speed from one end to the other end. The total oxidation time is 50 min. The electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0077] Dyeing treatment: After anodizing, the aluminum alloy substrate was ultrasonically treated, washed with water, and immersed in an organic dye tank for dyeing. The organic dye was Okuno Dye 502 with a concentration of 10 g / L, a temperature of 22°C, and a dyeing time of 5 min.
[0078] Sealing treatment: After dyeing, the aluminum alloy substrate is ultrasonically treated, washed with water and then put into a sealing tank. The sealing liquid brand is DX500 with a concentration of 10 g / L. The temperature is 93°C, the sealing time is 20 min, and then dried to obtain the metal part S2.
[0079] The pore size of the first porous layer of the metal member S2 is 7-12 nm, and the pore size of the second porous layer is 25-35 nm.
[0080] Example 3
[0081] This embodiment is used to illustrate the metal part and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0082] Pre-treatment: The aluminum alloy substrate is processed by CNC, grinding, polishing and other processes, and then degreased, neutralized and washed;
[0083] Anodizing: The aluminum alloy substrate after pretreatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing. The voltage of the first anodizing is 18 V, and the total oxidation time is 25 min. The aluminum alloy substrate is pulled out of the electrolyte surface at a uniform speed from one end to the other end. Then the voltage is adjusted to 9 V, and the aluminum alloy substrate is completely immersed in the electrolyte for oxidation for 50 min. The electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20 ° C.
[0084] Dyeing treatment: After anodizing, the aluminum alloy substrate was ultrasonically treated, washed with water, and immersed in an organic dye tank for dyeing. The organic dye was Okuno Dye 502 with a concentration of 10 g / L, a temperature of 22°C, and a dyeing time of 5 min.
[0085] Sealing treatment: After dyeing, the aluminum alloy substrate was ultrasonically treated, washed with water and then put into a sealing tank. The sealing liquid brand was DX500 with a concentration of 10 g / L. The temperature was 93°C, the sealing time was 20 min, and then dried to obtain the metal part S3.
[0086] The pore size of the first porous layer of the metal member S3 is 7-12 nm, and the pore size of the second porous layer is 25-35 nm.
[0087] Example 4
[0088] This embodiment is used to illustrate the metal part and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0089] Pre-treatment: The aluminum alloy substrate is processed by CNC, grinding, polishing and other processes, and then degreased, neutralized and washed;
[0090] Anodizing: The voltage of the first anodizing was 18V, and the aluminum alloy substrate (the length from one end of the aluminum alloy substrate to the other end was 16cm) after the pretreatment was uniformly immersed in the electrolyte from one end to the other end, and the total oxidation time was 25min; then the voltage was adjusted to 9V, and the aluminum alloy substrate was completely immersed in the electrolyte for 50min; wherein the electrolyte contained 80g / L sulfuric acid and 40g / L oxalic acid, and the oxidation temperature was 20℃;
[0091] Dyeing treatment: After anodizing, the aluminum alloy substrate was ultrasonically treated, washed with water, and immersed in an organic dye tank for dyeing. The organic dye was Okuno Dye 502 with a concentration of 10 g / L, a temperature of 22°C, and a dyeing time of 5 min.
[0092] Sealing treatment: After dyeing, the aluminum alloy substrate was ultrasonically treated, washed with water and then put into a sealing tank. The sealing liquid brand was DX500 with a concentration of 10 g / L. The temperature was 93°C, the sealing time was 20 min, and then dried to obtain the metal part S4.
[0093] The pore size of the first porous layer of the metal member S4 is 7-12 nm, and the pore size of the second porous layer is 25-35 nm.
[0094] Example 5
[0095] This embodiment is used to illustrate the metal part and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0096] Pre-treatment: The aluminum alloy substrate is processed by CNC, grinding, polishing and other processes, and then degreased, neutralized and washed;
[0097] Anodizing: The aluminum alloy substrate (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing. The voltage of the first anodizing is 18 V and the oxidation time is 25 min. Then the voltage is adjusted to 9 V, and the aluminum alloy substrate is pulled out of the electrolyte surface at a uniform speed from one end to the other end. The total oxidation time is 50 min. The electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0098] Sealing treatment: the aluminum alloy substrate was ultrasonically treated and washed with water and then put into a sealing tank. The sealing liquid brand was DX500 with a concentration of 10 g / L. The temperature was 93°C and the sealing time was 20 min. After drying, the metal part S5 was obtained.
[0099] The pore size of the first porous layer of the metal member S5 is 7-12 nm, and the pore size of the second porous layer is 25-35 nm.
[0100] The preparation steps of the metal part S6 of this embodiment are the same as those of Example 1, except for the anodizing treatment: the aluminum alloy substrate after pre-treatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing, the voltage of the first anodizing is 10 V, and the oxidation time is 40 min; then the voltage is adjusted to 8 V, so that the aluminum alloy substrate is pulled out of the electrolyte surface at a uniform speed from one end to the other end, and the total oxidation time is 80 min; wherein the electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0101] The pore size of the first porous layer of the metal member S6 is 3-8 nm, and the pore size of the second porous layer is 20-25 nm.
[0102] Example 7
[0103] The preparation steps of the metal part S7 of this embodiment are the same as those of Example 1, except for the anodizing treatment: the aluminum alloy substrate after pre-treatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing, the voltage of the first anodizing is 30 V, and the oxidation time is 10 min; then the voltage is adjusted to 12 V, so that the aluminum alloy substrate is pulled out of the electrolyte surface at a uniform speed from one end to the other end, and the total oxidation time is 40 min; wherein the electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0104] The pore size of the first porous layer of the metal member S7 is 8-15 nm, and the pore size of the second porous layer is 30-40 nm.
[0105] Comparative Example 1
[0106] The preparation steps of the metal part D1 of this comparative example are the same as those of Example 1, except for the anodizing treatment: the aluminum alloy substrate after pre-treatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in an electrolyte for the first anodizing, the voltage of the first anodizing is 18 V, and the oxidation time is 25 min; then the voltage is adjusted to 9 V, and the oxidation time is 50 min; wherein the electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0107] Comparative Example 2
[0108] The preparation steps of the metal part D2 of this comparative example are the same as those of Example 1, except for the anodizing treatment: the aluminum alloy substrate after pre-treatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in an electrolyte for anodizing, the anodizing voltage is 18 V, and the oxidation time is 25 min; wherein the electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0109] Comparative Example 3
[0110] The preparation steps of the metal part D3 of this comparative example are the same as those of Example 1, except for the anodizing treatment: the aluminum alloy substrate after pre-treatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in an electrolyte for anodizing, the anodizing voltage is 9 V, and the oxidation time is 50 min; wherein the electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0111] Comparative Example 4
[0112] The preparation steps of the metal part D4 of this comparative example are the same as those of Example 1, except for the anodizing treatment: the aluminum alloy substrate after pre-treatment (the length from one end of the aluminum alloy substrate to the other end is 16 cm) is immersed in the electrolyte for the first anodizing, the voltage of the first anodizing is 9 V, and the oxidation time is 25 min; then the voltage is adjusted to 18 V, and the aluminum alloy substrate is pulled out of the electrolyte surface at a uniform speed from one end to the other end, and the total oxidation time is 50 min; wherein the electrolyte contains 80 g / L sulfuric acid and 40 g / L oxalic acid, and the oxidation temperature is 20°C.
[0113] Performance Test:
[0114] Appearance effect: Use D65 light source to visually check whether the shell has a gradient ceramic texture at the same position.
[0115] Salt spray test:
[0116] 1. Salt water concentration: 5%, test temperature: 35℃, spray liquid pH value (35℃): pH 6.5-7.2. Spray pressure: 0.07-0.17 MPa, spray method: continuous spray, spray volume: 1.5±0.5㎖ / hr (funnel area 80cm 2 ) ;
[0117] 2. Sample placement method: Place the sample face up, and perform a 2mm X-Cutting test on all sections + one coating section after 48 hours.
[0118] Boiling test:
[0119] 1. Constant temperature water bath, temperature: 80℃±2℃, time 30min;
[0120] 2. Soak the test piece in a constant temperature water bath for 30 minutes, then remove the water with a rag, and then place it at room temperature for 4 hours.
[0121] 3. Draw a grid with 2 mm intervals on the test piece, stick the tape on it and pull it once in the vertical direction.
[0122] Table 1
[0123]
[0124] It can be seen from the results in Table 1 that the metal parts provided by the present invention can achieve a gradual change from ceramic texture to metal texture, and the gradual transition is natural, and has good wear resistance and corrosion resistance. The metal parts of the comparative example are not within the protection scope of the present invention and cannot achieve the appearance effect of the present invention.
[0125] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0126] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0127] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A metal part, characterized in that: include: A metal substrate and an anodic oxide film located on the surface of the metal substrate, wherein the anodic oxide film comprises a first porous layer located on the metal substrate and a second porous layer located on the first porous layer, the pore size of the first porous layer is 1-20 nm, the pore size of the second porous layer is 20-40 nm, and the thickness of the first porous layer or the second porous layer varies in a gradient; The metal substrate has a first end and a second end, and along an extending direction from the first end to the second end of the metal substrate, a thickness of the first porous layer or the second porous layer gradually decreases.
2. The metal part according to claim 1, characterized in that: Along the extending direction from the first end to the second end of the metal substrate, the thickness of the first porous layer gradually decreases.
3. The metal member according to claim 2, characterized in that: Along the extension direction from the first end to the second end of the metal substrate, the first porous layer has a starting end and an ending end, the thickness of the starting end of the first porous layer is 2-6 μm, and the thickness of the ending end of the first porous layer is 0-10 nm.
4. The metal part according to claim 3, characterized in that: The second porous layer has a thickness of 2-20 μm.
5. The metal member according to claim 1, characterized in that: Along the extending direction from the first end to the second end of the metal substrate, the thickness of the second porous layer gradually decreases.
6. The metal member according to claim 5, characterized in that: Along the extension direction from the first end to the second end of the metal substrate, the second porous layer has a starting end and an ending end, the thickness of the starting end of the second porous layer is 2-20 μm, and the thickness of the ending end of the second porous layer is 0-100 nm.
7. The metal member according to claim 6, characterized in that: The thickness of the first porous layer is 2-6 μm.
8. The metal member according to claim 1, characterized in that: The metal substrate includes aluminum or an aluminum alloy.
9. The metal member according to claim 1, characterized in that: A sealing layer is provided on the surface of the anodized film away from the metal substrate.
10. The method for preparing a metal part according to any one of claims 1 to 9, characterized in that: The steps include: Immersing the metal substrate in an electrolyte for a first anodization to form a second porous layer on the metal substrate, and immersing the metal substrate having the second porous layer in the electrolyte for a second anodization to form a first porous layer between the metal substrate and the second porous layer, wherein the voltage of the first anodization is 10-30V, and the voltage of the second anodization is 8-12V; Wherein, during the first anodization, the time for which different regions of the metal substrate are immersed in the electrolyte is controlled to change gradually so that the thickness of the second porous layer changes gradually, or, during the second anodization, the time for which different regions of the metal substrate are immersed in the electrolyte is controlled to change gradually so that the thickness of the first porous layer changes gradually.
11. The preparation method according to claim 10, characterized in that: The total oxidation time of the first anodization is 10-40 minutes.
12. The preparation method according to claim 10, characterized in that: The total oxidation time of the second anodization is 40-100 minutes.
13. The preparation method according to claim 10, characterized in that: The electrolyte includes: 20-200 g / L sulfuric acid and 0-50 g / L organic acid.
14. The preparation method according to claim 10, characterized in that: Before the first anodizing treatment is performed, the metal substrate is pre-treated, and the pre-treatment includes at least one or more of CNC, grinding, polishing, sandblasting, degreasing, neutralization and water washing.
15. The preparation method according to claim 10, characterized in that: After the second anodization, the anodized film is sealed.
16. An electronic product housing, characterized in that: Comprising the metal part as described in any one of claims 1-9.
Citation Information
Patent Citations
Aluminum alloy and preparation method thereof and mobile phone shell
CN109208055A
Method of coloring anodized coating, and colored member
JP2010270351A